Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1101/2020.03.04.20031120
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Human Kidney is a Target for Novel Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Infection

Abstract: BACKGROUND The outbreak of a novel coronavirus (SARS-CoV-2, previously provisionally named 2019 novel coronavirus or 2019-nCoV) since December 2019 in Wuhan, China, has become an emergency of major international concern. Apart from the respiratory system, it is unclear whether SARS-CoV-2 can also directly infect other tissues such as the kidney or induce acute renal failure. METHODS We conducted a retrospective analysis of estimated glomerular filtration rate (eGFR) along with other clinical parameters from 85… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
526
3
32

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 460 publications
(608 citation statements)
references
References 23 publications
(32 reference statements)
26
526
3
32
Order By: Relevance
“…of SARS-CoV-2 were very high in nasopharyngeal swab during the first week of symptoms, with peak on day 4 post-onset, whereas the peak value appeared until 7-10 days post-onset with much lower RNA copies during SARS-CoV and MERS-CoV infection [6,[18][19][20]. Second, the presence of virus RNA in lower respiratory tract (sputum or BALs), stool, and blood samples were reported, and the kinetics of virus shedding in these sites were distinct from that in throat [8][9][10][11]. Third, sampling error and the technical limitations of RT-PCR sometimes led to a false testing result [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…of SARS-CoV-2 were very high in nasopharyngeal swab during the first week of symptoms, with peak on day 4 post-onset, whereas the peak value appeared until 7-10 days post-onset with much lower RNA copies during SARS-CoV and MERS-CoV infection [6,[18][19][20]. Second, the presence of virus RNA in lower respiratory tract (sputum or BALs), stool, and blood samples were reported, and the kinetics of virus shedding in these sites were distinct from that in throat [8][9][10][11]. Third, sampling error and the technical limitations of RT-PCR sometimes led to a false testing result [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, pathogenic cure in terms of viral RNA-conversion, had to be reached before patients being discharged from hospitals for the purpose of disease control, at least in China. The kinetics of viral shedding [6,7], the possible presence of viral RNA in multiple sites [8][9][10][11], sampling error and the technical limitations of RT-PCR sometimes led to a false testing result [12,13], posing a great challenge to discharge management after obtaining clinical cure. Nevertheless, a recent investigation reported that the median duration of viral shedding was 20 days after disease onset for patients infected with SARS-CoV-2 [4].…”
Section: Introductionmentioning
confidence: 99%
“…In these patients, early aggressive volume resuscitation is indicated to avoid development of extensive acute tubular injury due to prolonged severe renal hypoperfusion. While it has been suggested that direct cellular injury via ACE-2 that is expressed in proximal renal tubules could contribute to AKI, 21 it remains likely that shock (and in some cases cytokine storm) are the primary causes of acute tubular necrosis in this setting. Moreover, similar to right-sided heart failure, following aggressive fluid administration the increased right atrial pressure is transmitted retrograde, leading to elevated venous pressure in abdominal organs such as the kidney, liver, and the guts.…”
Section: Acquired Volume Overloadmentioning
confidence: 99%
“…Indeed, a clinical study reported that 27.06% of patients with COVID-19 exhibited acute renal failure (ARF), while elderly patients (≥60 years) were more likely to develop ARF (65.22% vs 24.19%) (8). A further immunohistochemistry analysis revealed that the antigen for 2019-nCoV accumulates in renal tubules (8). Another clinical study with 59 COVID-19 patients showed that proteinuria occurred in 63% of patients (9).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that ACE2 is highly expressed in renal tubular cells, implying that 2019-nCoV may directly bind to ACE2-positive cells in the kidney and thus induce kidney injuries (7). Indeed, a clinical study reported that 27.06% of patients with COVID-19 exhibited acute renal failure (ARF), while elderly patients (≥60 years) were more likely to develop ARF (65.22% vs 24.19%) (8). A further immunohistochemistry analysis revealed that the antigen for 2019-nCoV accumulates in renal tubules (8).…”
Section: Introductionmentioning
confidence: 99%